Edukasi Pengenalan Warna Melalui Kegiatan Mewarnai untuk Meningkatkan Motorik Halus pada Anak Usia Dini - Roudlotun Nurul Laili; Muhammad Nashir; Muhammad Al Amin; Erik Toga (FKIP, Universitas Palangka Raya, 2023)
Early childhood education is crucial in laying the foundation for children's cognitive, emotional, and physical development. A vital aspect of this education is the introduction of colors and the developing of fine motor skills, which can be enhanced through coloring activities. This community service activity aimed to provide color recognition education through coloring activities to improve fine motor skills in early childhood. The targets in this activity are early childhood children (2-5 years old) and BKB cadres at Taman Posyandu (Tapos) Ceria Desa Rejosari, Glagah District, Banyuwangi. The methods used are lecturing, drilling, and mentoring. The results of this activity are that children can recognize, distinguish, and name various colors, children's fine motor skills, such as eye-hand coordination and hand movement control, are improved through coloring activities, and they can express themselves and their ideas through the strokes of color they pour on the given picture. Recognizing colors and developing fine motor skills are crucial foundations for supporting young children in preparing important skills for the following learning stages, such as reading and writing. Coloring activities can become a positive habit, encouraging children to spend time with productive and educational activities.